(untitled) (Al-Farooq Journal of Sciences, 2026)
Immanuel Kant’s philosophy of art centers on shifting the aesthetic focal point from the object to the subject, viewing beauty as a mental state arising from the free play and harmony between the faculties of imagination and understanding. His inquiry begins by establishing the autonomy of art, where he distinguishes fine art from handicrafts (mercenary art) and the sciences. For Kant, art is a free activity akin to play; it does not submit to rigid demonstrative rules but rather possesses a purposiveness without a purpose. In his analysis of the sublime, Kant differentiates between the Beautiful, which evokes tranquility, and the Sublime, which incites awe. The sublime is divided into two types: the Mathematical Sublime, related to a magnitude so vast that the senses fail to perceive it, prompting the Reason to intervene and comprehend the infinite; and the Dynamical Sublime, linked to the formidable forces of nature that awaken our consciousness of moral superiority and spiritual independence over matter. To resolve the dilemma of how art can be produced without preexisting rules, Kant introduces the Theory of Genius as the innate talent through which nature gives the rule to art, ensuring originality and exemplarity. He concludes his vision by linking beauty to morality, regarding art as a symbol of the morally good, as the aesthetic experience refines the soul and prepares it for disinterestedness and freedom. The impact of this philosophy served as the cornerstone of German Idealism; Schelling elevated art to the supreme organon of philosophy, while Hegel transformed it into a manifestation of the Spirit through history. In the modern era, Kantian aesthetic autonomy paved the way for Art for Art’s Sake and Abstract movements, extending into Postmodernism, which revived the concept of the Sublime to interpret contemporary arts based on shock and the transcendence of traditional perception. Thus, Kant remains the primary legislator for the sovereignty of art and the freedom of creativity.